Dysregulation of the Mitochondrial Proteome Occurs in Mice Lacking Adiponectin Receptor 1 - Pepin, Mark E.; Koentges, Christoph; Pfeil, Katharina; Gollmer, Johannes; Kersting, Sophia; Wiese, Sebastian; Hoffmann, Michael M.; Odening, Katja E.; Mühlen, Constantin von zur; Diehl, Philipp; Stachon, Peter; Wolf, Dennis; et al. (Frontiers in Endocrinology, 2019)
Decreased serum adiponectin levels in type 2 diabetes has been linked to the onset of mitochondrial dysfunction in diabetic complications by impairing AMPK-SIRT1-PGC-1α signaling via impaired adiponectin receptor 1 (AdipoR1) signaling. Here, we aimed to characterize the previously undefined role of disrupted AdipoR1 signaling on the mitochondrial protein composition of cardiac, renal, and hepatic tissues as three organs principally associated with diabetic complications. Comparative proteomics were performed in mitochondria isolated from the heart, kidneys and liver of Adipor1−/− mice. A total of 790, 1,573, and 1,833 proteins were identified in cardiac, renal and hepatic mitochondria, respectively. While 121, 98, and 78 proteins were differentially regulated in cardiac, renal, and hepatic tissue of Adipor1−/− mice, respectively; only 15 proteins were regulated in the same direction across all investigated tissues. Enrichment analysis of differentially expressed proteins revealed disproportionate representation of proteins involved in oxidative phosphorylation conserved across tissue types. Curated pathway analysis identified HNF4, NRF1, LONP, RICTOR, SURF1, insulin receptor, and PGC-1α as candidate upstream regulators. In high fat-fed non-transgenic mice with obesity and insulin resistance, AdipoR1 gene expression was markedly reduced in heart (−70%), kidney (−80%), and liver (−90%) (all P < 0.05) as compared to low fat-fed mice. NRF1 was the only upstream regulator downregulated both in Adipor1−/− mice and in high fat-fed mice, suggesting common mechanisms of regulation. Thus, AdipoR1 signaling regulates mitochondrial protein composition across all investigated tissues in a functionally conserved, yet molecularly distinct, manner. The biological significance and potential implications of impaired AdipoR1 signaling are discussed.